2014
DOI: 10.4103/0019-5049.130813
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine decreases the requirement of ketamine and propofol during burns debridement and dressings

Abstract: Background and Aims:Dexmedetomidine (Dex), a highly selective α2-adrenoreceptor agonist, is used for sedation management in various clinical settings and shows anaesthetic-sparing effect. Our aim was to study the effects of Dex on requirements of propofol, ketamine, and intraoperative haemodynamic variations during burns debridement and dressing changes, and compare its effectiveness and safety with combination of ketamine and propofol.Methods:Sixty adult patients posted for elective debridement and dressing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…The affinity of the S ‐enantiomer to the NMDA receptor is two times higher than that of racemic ketamine and four times higher than that of the R ‐enantiomer . Medetomidine is an α 2 ‐adrenergic receptor agonist used for sedation and anesthetic premedication and, because of its anesthetic‐sparing effect, it is applied as anesthetic adjuvant . Low analgesic and myorelaxation effects have also been observed .…”
Section: Introductionmentioning
confidence: 99%
“…The affinity of the S ‐enantiomer to the NMDA receptor is two times higher than that of racemic ketamine and four times higher than that of the R ‐enantiomer . Medetomidine is an α 2 ‐adrenergic receptor agonist used for sedation and anesthetic premedication and, because of its anesthetic‐sparing effect, it is applied as anesthetic adjuvant . Low analgesic and myorelaxation effects have also been observed .…”
Section: Introductionmentioning
confidence: 99%
“…There was sta s cally significant difference between the groups as per Student t-test (p<0.05). Ravipa P et al [13] observed Time to recovery was 9.57 ± 1.50 min in the Dex group which was significantly lower than in the control group 11.53 ± 2.56 min (P = 0.0006). (Figure no.6) It was observed that dose requirement of Ketamine (228.8±21.9) and Propofol (263.2 ± 22.5) was significantly more in Group A as compared to Group B (101.1±20.3 and 120.8±22.4 respec vely).…”
Section: Discussionmentioning
confidence: 86%
“…(Figure no.1) The gender distribu on in the two groups as per Fisher's test were comparable and sta s cally not significant (p>0.05). 40 % and 39% pa ents were females in Group A and B respec vely (Figure no.2)Ravipa P et al [13] observed there was no sta s cally significant difference in the demographic and clinical characteriscs among the two groups. It was observed that intraopera vely the heart rate, systolic and diastolic Blood pressure was significantly higher in Group A as compared to Group B.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The few published investigations of procedural sedation in adults are encouraging [47,48] but the place of these combinations in the sedation of obese adult ICU patients requires more investigation before conclusions may be reached and recommendations issued. Matters in need of consideration include determination of the optimal dose ratios and structured appraisal of adverse reactions [49].…”
Section: Commentarymentioning
confidence: 99%